A pilot study examining garment severance damage caused by a trained sharp-weapon user - Cowper, Elizabeth J.; Mahoney, Peter F.; Godhania, K.; Carr, Debra J.; Harrison, Karl (Cranfield University, 2016)
The pilot study summarized in this paper aimed to raise awareness of a gap that exists in the forensic textile science literature about damage caused to clothing by trained sharp-weapon users. A male trained in the Filipino martial arts discipline of Eskrima performed attack techniques on a physical model of a male torso covered with a 97% cotton/3% elastane knitted T-shirt, that is, a garment commonly worn by males. Fabric severance appearance created by three different, but commonly available, knives was evaluated. High-speed video was used to capture each attack. After each attack the resulting damage to the garment was assessed. This pilot study highlighted differences in severances associated with weapon selection, that is, not all knives resulted in similar patterns of textile damage. In addition, a mixture of stab and slash severances were observed. The findings demonstrated the possible misinterpretation of textile damage under these circumstances compared to damage patterns reported in the existing forensic textile science literature for more commonly occurring knife attacks (i.e. stabbings).
Keywords: textile damage; simulant; T-shirt; martial arts; knife